2011
DOI: 10.1111/j.1600-0412.2011.01178.x
|View full text |Cite
|
Sign up to set email alerts
|

Progestin treatment for the prevention of preterm birth

Abstract: Progestin supplementation appears to be a promising approach to both preventing initiation of preterm labor and treating it once it is already established, given progesterone’s role in maintaining pregnancy as well as support from basic and clinical research. Progesterone and 17- alpha-hydroxyprogesterone-acetate (17-OH P) slow the process of cervical ripening and this is the rationale for prophylactic long-term progestin supplementation mostly studied so far. However, progesterone (but not 17-OH P) also inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 82 publications
0
15
1
Order By: Relevance
“…Similarly, earlier studies did not find any non-genomic relaxing effect for P4 either [35], although a synthetic P4 derivative, dydrogesterone was found to inhibit the pregnant myometrial contractions by the inhibition of voltage dependent Ca-channels [33]. Some other experiments found that P4 had an ability to relax human non-pregnant or pregnant uterine tissues in high dose [36][37][38] which findings are virtually in conflict of our results. However, the findings may be a result of genomic feature of P4 since the P4 incubation period in both reported studies were more than 1 h. The specific receptor antagonists of sex hormones (flutamide for T and fulvestrant for E2) did not reduce their actions, which is further evidence that the genomic pathway is not involved in the relaxing effects of T and E2.…”
Section: Discussioncontrasting
confidence: 75%
“…Similarly, earlier studies did not find any non-genomic relaxing effect for P4 either [35], although a synthetic P4 derivative, dydrogesterone was found to inhibit the pregnant myometrial contractions by the inhibition of voltage dependent Ca-channels [33]. Some other experiments found that P4 had an ability to relax human non-pregnant or pregnant uterine tissues in high dose [36][37][38] which findings are virtually in conflict of our results. However, the findings may be a result of genomic feature of P4 since the P4 incubation period in both reported studies were more than 1 h. The specific receptor antagonists of sex hormones (flutamide for T and fulvestrant for E2) did not reduce their actions, which is further evidence that the genomic pathway is not involved in the relaxing effects of T and E2.…”
Section: Discussioncontrasting
confidence: 75%
“…The route of administration may influence the efficacy of progesterone therapy during pregnancy [ 22 , 23 ]. Vaginal progesterone administration resulted in higher endometrial progesterone concentrations than those observed in patients administered oral and intramuscular progesterone [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral and vaginal administration routes are noninvasive, whereas intramuscular administration is invasive. Additionally, the oral and vaginal routes of administration are associated with acceptable and minimal side effects, respectively, whereas side effects were reported in one-third of pregnant women who received weekly intramuscular injections of progesterone to prevent recurrent preterm delivery [ 22 24 ]. Oral synthetic progestational agents, including dydrogesterone, have been developed to eliminate issues related to the variable bioavailability of natural formulations of oral progesterone [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…414 Studies have suggested that progestin supplementation may prevent initiation of preterm labor or treat it once it is already established. 415 Whether changes in MMPs and sex hormones could interfere with uterine relaxation and trigger uterus contraction and pre-term delivery needs to be further examined. Also, whether the potential beneficial effects of progesterone in preterm labor are mediated via modulation of MMP expression/activity warrant further investigation.…”
Section: Dysregulation Of Uterine Mmps During Preterm Labormentioning
confidence: 99%